Evaluating Mismatch Repair Deficiency in Pancreatic Adenocarcinoma: Challenges and Recommendations - Hu, Zishuo I; Shia, Jinru; Stadler, Zsofia K; Varghese, Anna M; Capanu, Marinela; Salo-Mullen, Erin; Lowery, Maeve A; Diaz, Jr, Luis A; Mandelker, Diana; Yu, Kenneth H; Zervoudakis, Alice; Kelsen, David P; et al. (Clinical cancer research, 2018)
Immune checkpoint inhibition has been shown to generate profound and durable responses in mismatch repair deficient (MMR-D) solid tumors and has elicited interest in detection tools and strategies to guide therapeutic decision-making. Herein we address questions on the appropriate screening, detection methods, patient selection, and initiation of therapy for MMR-D pancreatic ductal adenocarcinoma (PDAC) and assess the utility of next-generation sequencing (NGS) in providing additional prognostic and predictive information for MMR-D PDAC. Archival and prospectively acquired samples and matched normal DNA from = 833 PDAC cases were analyzed using a hybridization capture-based, NGS assay designed to perform targeted deep sequencing of all exons and selected introns of 341 to 468 cancer-associated genes. A computational program using NGS data derived the MSI status from the tumor-normal paired genome sequencing data. Available germline testing, IHC, and microsatellite instability (MSI) PCR results were reviewed to assess and confirm MMR-D and MSI status. MMR-D in PDAC is a rare event among PDAC patients (7/833), occurring at a frequency of 0.8%. Loss of MMR protein expression by IHC, high mutational load, and elevated MSIsensor scores were correlated with MMR-D PDAC. All 7 MMR-D PDAC patients in the study were found to have Lynch syndrome. Four (57%) of the MMR-D patients treated with immune checkpoint blockade had treatment benefit (1 complete response, 2 partial responses, 1 stable disease). An integrated approach of germline testing and somatic analyses of tumor tissues in advanced PDAC using NGS may help guide future development of immune and molecularly directed therapies in PDAC patients. .